The Role of The Drug and Food Supervisory Agency (BPOM) on The Difference of Clorined Vinylers Reviewed From Law Number 8 of 1999 Consumer Protection - Anisa Vidya Sasmita (Faculty of Law, Merdeka University Surabaya, 2019)
The purpose of thisis to know about the role of BPOM in consumers for the circulation of chlorinated sanitary napkins which are reviewed from the UUPK and how the role of BPOM is in accordance with the provisions of the applicable legislation. The Indonesian Consumers Foundation (which was later abbreviated as YLKI) has tested the chlorine content in the Charm brand sanitary napkin which is a product of PT. Indonesian Charm Union. The YLKI test results found the highest chlorine content in this brand, namely (54.73 ppm). Based on the provisions of the Food and Drug Administration (FDA) the United States has recommended that the maximum chlorine limit in sanitary napkins is 0.1 ppm. Consumers who have used the Charm pads in the long term can cause reproductive health problems, such as vaginal discharge, hives, irritation, and even can causecancer cervical.